A novel fungal strain, Bjerkandera adusta BK-1, as a promising broad-spectrum biological control agent against plant fungal diseases. Issue 4 (3rd April 2022) - Chen, Yuhong; Wan, Yunbao; Jiang, Xuefei; Liu, Qian; Wei, Tao; Wang, Maolin
ABSTRACT: In this study, we aimed to investigate the biopesticide activity of a novel fungal strain Bjerkandera adusta BK-1. The in vitro inhibitory potential of BK-1 against six species of identified phytopathogenic fungi was evaluated using a dual culture assay. In addition, in-planta treatment with BK-1 as a fungicide significantly reduced plant disease symptoms, such as grey mould, brown spot, and early blight disease. Furthermore, the colonisation ability of BK-1 in soil and leaves was also found to be stable. Overall, BK-1 has practical value as a novel, promising broad-spectrum biocontrol agent against multiple plant fungal diseases.